Obesity and Sex Affect the Immune Responses to Tick-Borne Encephalitis Booster Vaccination - Garner-Spitzer, Erika; Poellabauer, Eva-Maria; Wagner, Angelika; Guzek, Angela; Zwazl, Ines; Seidl-Friedrich, Claudia; Binder, Christoph J.; Stiasny, Karin; Kundi, Michael; Wiedermann, Ursula (Frontiers in Immunology, 2020)
Obesity has dramatically increased over the last 30 years and reaches according to World Health Organization dimensions of a global epidemic. The obesity-associated chronic low-level inflammation contributes to severe comorbidities and directly affects many immune cells leading to immune dysfunction and increased susceptibility to infections. Thus, prophylaxis against vaccine-preventable diseases is crucial, yet the responsiveness to several vaccines is unclear under obesity. In order to assess the responsiveness to tick-borne encephalitis (TBE) vaccine, we revaccinated 37 obese individuals and 36 normal-weight controls with a licensed TBE vaccine. Metabolic, hormonal, and immunologic profiles along with vaccine-specific humoral and cellular immune responses were evaluated in sera and peripheral blood mononuclear cells (PBMCs) before, 1 week, 4 weeks, and 6 months after TBE booster. Obese adults had significantly increased metabolic (triglycerides, cholesterol ratios, leptin, insulin) and proinflammatory (C-reactive protein) parameters. They showed stronger initial increase of TBE-specific Ab titers (d7_d28) followed by a significantly faster decline after 6 months, which correlated with high body mass index and leptin and insulin levels. The fold increase of Ab-titer levels was significantly higher in obese compared to control males and linked to reduced testosterone levels. Obesity also affected cellular responses: PBMCs of the obese vaccinees had elevated interleukin 2 and interferon γ levels upon antigen stimulation, indicating a leptin-dependent proinflammatory TH1 polarization. The expansion of total and naive B cells in obese might explain the initial increase of Ab titers, whereas the reduced B-memory cell and plasma blast generation could be related to fast Ab decline with a limited maintenance of titers. Among T follicular helper cell (Tfh) cells, the Tfh17 subset was significantly expanded particularly in obese males, where we observed a strong initial Ab increase. Systemic but not local vaccine side effects were more frequent in obese subjects as a possible consequence of their low-grade proinflammatory state. In summary, TBE booster vaccination was effective in obese individuals, yet the faster Ab decline could result in a reduced long-term protection. The sex-based differences in vaccine responses indicate a complex interplay of the endocrine, metabolic, and immune system during obesity. Further studies on the long-term protection after vaccination are ongoing, and also evaluation of primary vaccination against TBE in obese individuals is planned. Clinical Trial Registration: NCT04017052; https://clinicaltrials.gov/ct2/show/NCT04017052.